1989
DOI: 10.1177/089124389003004004
|View full text |Cite
|
Sign up to set email alerts
|

Fraternities and Rape on Campus

Abstract: Despite widespread knowledge that fraternity members are frequently involved in the sexual assaults of women, fraternities are rarely studied as social contexts-groups and organizations-that encourage the sexual coercion of women. An analysis of the norms and dynamics of the social construction of fraternity brotherhood reveals the highly masculinist features of fraternity structure and process, including concern with a narrow, stereotypical conception of masculinity and heterosexuality; a preoccupation with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(123 citation statements)
references
References 13 publications
2
121
0
Order By: Relevance
“…One of the most significant differences is related to sexual behavior. Previous research suggests that a double standard existed-and may still exist-regarding what is considered "acceptable" behavior for men and women (Laumann, Gagnon, Michael, & Michaels, 1994;Martin & Hummer, 1989). Whereas men who engage in many casual sexual encounters are considered "studs", women have been expected to limit their number of partners to avoid earning a bad reputation (Bogle, 2008;Harding & Jencks, 2003;Reiss, 1997).…”
Section: Gendermentioning
confidence: 99%
“…One of the most significant differences is related to sexual behavior. Previous research suggests that a double standard existed-and may still exist-regarding what is considered "acceptable" behavior for men and women (Laumann, Gagnon, Michael, & Michaels, 1994;Martin & Hummer, 1989). Whereas men who engage in many casual sexual encounters are considered "studs", women have been expected to limit their number of partners to avoid earning a bad reputation (Bogle, 2008;Harding & Jencks, 2003;Reiss, 1997).…”
Section: Gendermentioning
confidence: 99%
“…Sexual violence, including MPR, on campus and in fraternity settings has been examined by a few authors (Ehrhart & Sandler, 1985;Humphrey & Kahn, 2000;Martin & Hummer;1989;Sanday 2007). Most of these authors identified various conditions that they believed could facilitate sexual violence committed by fraternity men.…”
Section: Situational Factorsmentioning
confidence: 99%
“…An often held assumption is that fraternity and sports membership are significant correlates for perpetrating sexually aggressive acts, largely due to hyper masculine beliefs, secrecy, and peer pressure (Boeringer, 1996;Martin & Hummer, 1989). Recent research has found, however, that fraternity and sports membership has more of an indirect effect based upon those groups' emphasis on maintaining secrecy and peer pressure as related to sexual behaviors (Franklin, Bouffard, & Pratt, 2012).…”
Section: College Life and Risk Factors For Victimizationmentioning
confidence: 99%